MODEL PEMBELAJARAN TARI BAGI ANAK TUNAGRAHITA - Heni Siswantari; Devi Paleta (FIP Unimed, 2020)
ABSTRACKChildren with mental retardation have below-average intelligence, limited intelligence, and social communication inability. Children with mental retardation have changing interests and emotions. The purpose of this study was to find out the dance learning model so that it would facilitate the teaching of dance to children with mental retardation. This research was a descriptive qualitative type subjected to students and dance teachers based on purposive sampling. The object of the study is the dance learning model for children with mental retardation in SLB Negeri Pembina Yogyakarta. Data collection through observation, interview, and documentation techniques. The validity of the data by triangulation of sources and methods using the interactive data analysis of the inductive model of Miles and Huberman. The result of the study shows that 1) Dance extracurricular activities at SLB Negeri Pembina aim to develop talents and interests, improve motor skills, socialization, and self-confidence of children. 2) Learning models that are applied are the teacher center learning approach with materials that are tailored to the ability level of children with mental retardation. The method used is a demonstration, and drill with Cooperative Learning and Direct Instruction strategies. Keywords: Dance Learning Model, children with mental retardation, SLB Negeri Pembina ABSTRAKAnak retardasi mental memiliki kecerdasan di bawah rata-rata, kecerdasan terbatas, dan ketidakmampuan komunikasi sosial. Anak retardasi mental mengalami perubahan minat dan emosi. Tujuan penelitian ini adalah untuk mengetahui model pembelajaran tari agar dapat memfasilitasi pembelajaran tari pada anak tunagrahita. Jenis penelitian ini adalah deskriptif kualitatif dengan subjek siswa dan guru tari berdasarkan purposive sampling. Objek penelitiannya adalah model pembelajaran tari pada anak tunagrahita di SLB Negeri Pembina Yogyakarta. Pengumpulan data melalui teknik observasi, wawancara, dan dokumentasi. Validitas data dengan triangulasi sumber dan metode menggunakan analisis data interaktif model induktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa 1) Kegiatan ekstrakurikuler tari di SLB Negeri Pembina bertujuan untuk mengembangkan bakat dan minat, meningkatkan keterampilan motorik, sosialisasi, dan kepercayaan diri anak. 2) Model pembelajaran yang diterapkan adalah pendekatan pembelajaran Teacher Center dengan materi yang disesuaikan dengan tingkat kemampuan anak tunagrahita. Metode yang digunakan adalah demonstrasi, dan drill dengan strategi Cooperative Learning dan Direct Instruction. Kata Kunci: Model Pembelajaran Tari, Anak tunagrahita, SLB Negeri Pembina